Archeologia awangardą nauk ścisłych. O formie kalibrowanych dat 14C - Walanus, Adam (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2005)
P. 129-133 ; 25 cm
Bibliography p. 132-133
English summary
Keywords: dating methods; radiocarbon dating

Archeologia Polski. Vol. 11 (1966) No 2, Recenzje i omówienia - Bronicka-Rauhut, Jadwiga. Reviewer (Zakład Narodowy im. Ossolińskich, 1966)
J. G. D. Clark, Radiocarbon dating and the spread of farming economy, "Antiquity", v. 39 : 1965, No 153, s. 45-48
P. 444-448 ; 25 cm
Bibliographical footnotes
Keywords: dating methods; radiocarbon dating; prehistoric farming

Archeologia Polski. Vol. 5 (1960) No 2, Reviews - Więckowska, Hanna (1927–2013). Reviewer (Zakład Narodowy im. Ossolińskich, 1960)
Henryk Tauber, Difficulties in the application of C 14 results in archaeology, „Archaeologia Austriaca”, Wien 24 : 1958, s. 59-69
P. 346-348 ; 25 cm
Keywords: radiocarbon dating; radiocarbon dating -- interpretation

Korygowanie chronologii C14 metodą dendrochronologiczną (stan badań) - Paderewska, Ludmiła (Zakład Narodowy im. Ossolińskich, 1977)
P. 263-299 : ill., maps, diagrams ; 25 cm
Bibliography p. 293-298
English or French summaries
Keywords: history of researches; dating methods; radiocarbon dating; dendrochronology

Zagadnienia podstawowe interpretacji wyników pomiarów fizycznych na przykładzie datowań metodą 14C - Walanus, Adam (Zakład Narodowy im. Ossolińskich, 1983)
P. 7-17 : ill. ; 25 cm
Bibliography p. 16
English summary
Keywords: dating methods; radiocarbon dating; radiocarbon dating -- interpretation

Zespoły datowane metodą 14C : From the Editor - Wiślański, Tadeusz (1931–1989) (Polska Akademia Nauk. Instytut Historii Kultury Materialnej, 1989)
29 cm
Keywords: absolute chronology; radiocarbon dating

Nowa krzywa lichenometryczna dla polskiej części Karpat = A new lichenometric curve for the Polish part of the Tatra Mountains - Kędzia, Stanisław (IGiPZ PAN, 2013)
24 cm
Keywords: lichens; lichenometric dating; lichenometric curve; Tatra Mountains

Debris flow activity in the Slovak part of the High Tatras in the light of lichenometric dating - Kędzia, Stanisław. Autor; Hreško, Juraj. Autor; Bugár, Gabriel. Autor (IGiPZ PAN, 2023)
Rock walls and talus slopes, which are the most common features of high-mountain relief, have been researched for many years. Geomorphologists have taken particular interest in debris flows, which play a major role in the development of talus slopes. This paper presents the results of the first lichenometric dating of debris flows on the southern slopes of the Tatra Mountains. The greatest debris flow activity took place in the Little Ice Age and in the last two decades.
24 cm
Keywords: lichenometric dating; debris flows; High Tatra Mountains

Aktywność spływów gruzowych w polskiej części Karkonoszy w świetle badań lichenometrycznych = The activity of debris flows in the Polish part of the Karkonosze Mountains in the light of lichenometric measurements - Kędzia, Stanisław; Parzóch, Krzysztof (IGiPZ PAN, 2016)
While 70 forms created by debris flows have been mapped for the Polish part of the Karkonosze Mountains, only 14 of these have a known time of origin and have been described in available literature. The oldest registered and described flows occurred in 1964, as followed by further events in 1994, 1997, 2001, 2002 and 2006. In 2011-2012 and 2014. Lichenometric measurements were carried out for the forms created by debris flows in the Karkonosze Mountains, i.e. the Great Snowy Cirque, the Black Cirque of Jagniątków, the Small Tarn Cirque, the Łomniczka Cirque and the White Jar nivation niche, in order to investigate levels of activity over the past 150 years. The lichenometric dating was based around lichens of the Rhizocarpon group. A major obstacle proved to be the limited amounts of lichens, or even their total absence in the case of the youngest forms created by debris flows. An exception was the Łomniczka Cirque. On the basis of the lichenometric dating it proved possible to identify three phases to the activity of Karkonosze debris flows. The first of these was characterised by a high intensity of the processes studied, and was associated with the Little Ice Age. As in the Tatra Mountains, this phase was seen to end in the 1920s, and was followed by a period of relative calm, interspersed with a small number of debris flows in the 1930s and 40s, and then in 1964. The next phase of increased activity as regards the transport of rock material within the forms created by flows (and including new debris flows), began in the 1980s, and has continued through to the present day. The debris flows in the Polish part of the Karkonosze Mountains are thus characterised by a course of activity similar to that noted in the Tatra Mountains.
24 cm
Keywords: cirques; debris flows; lichenometric dating; Karkonosze Mountains

Siedem kartek, siedem nieszczęść. Fragmenty dziennika Marii z Trębickich Faleńskiej w zbiorach Biblioteki Narodowej - Bąbel, Agnieszka (Wydawnictwo IBL PAN, 2017)
24 cm
Keywords: Faleńska, Maria; diary; dating; observation

Chronometria radiowęglowa jako metoda badawcza w archeologii : możliwości, ograniczenia, perspektywy - Pazdur, Anna; Pazdur, Mieczysław F. (1946–1995) (Polska Akademia Nauk. Instytut Historii Kultury Materialnej, 1983)
Celem artykułu jest przedstawienie aktualnego stanu chronometrii radiowęglowej, jej podstawowych założeń, niektórych zagadnień technicznych, źródeł błędów i możliwości ich eliminacji, zagadnień związanych z interpretacją wyników datowań, ze szczególnym uwzględnieniem specyficznych wymagań związanych ze stosowaniem metody radiowęglowej w badaniach archeologicznych. W rozdziale poświęconymfizycznym podstawom metody omówiono historyczny rozwój chronometrii radiowęglowej, sformułowano podstawowe założenia, przedstawiono zasadę pomiaru aktywności izotopu 14C oraz obliczania wieku, jak również perspektywy związane z wykorzystaniem akceleratorów do precyzyjnych pomiarów koncentracji 14C w próbkach naturalnych. Główna część artykułu poświęcona jest krytycznej analizie błędów chronometrii radiowęglowej oraz omówieniu ich źródeł i możliwości eliminacji lub minimalizacji. Z zagadnień tych wyodrębniony został - jako szczególnie ważny - problem kalibracji radiowęglowej skali czasu. Omówiono najistotniejsze cechy sześciu spośród istniejących opracowań opartych na skali dendrochronologicznej Pinus aristata, dokonano też podsumowania najnowszych badań prowadzonychw Europie, wykorzystujących pływające chronologie dębów kopalnych. W ostatnim rozdziale przedstawiono zagadnienia probabilistycznejinterpretacji wyników datowań radiowęglowych, konsekwencje tej interpretacji przy porównywaniu dat oraz charakterystykę najważniejszych problemów występujących podczas datowania poszczególnych okresów pradziejów
ill. ; 29 cm
Keywords: radiocarbon dating; radiocarbon dating -- interpretation; calibration; dendrochronology; oak woods

Archeologia Polski. Vol. 5 (1960) No 2, Reviews - Więckowska, Hanna (1927–2013). Reviewer (Zakład Narodowy im. Ossolińskich, 1960)
H. Gross, Die bisherigen Ergebnisse von C14-messungen und paläonologischen Untersuchungen für die Gliderung und Chronologie des Jungpleistozans in Mitteleuropa und den Nachbargebieten, “Eiszeitalter u. Gegenwart”, vol. 9 : 1958, p. 155-187
P. 348-350 ; 25 cm
Keywords: late Pleistocene -- central Europe; radiocarbon dating; radiocarbon dating -- interpretation

Radiocarbon dating of Neolithic assemblages from Bronocice - Kruk, Janusz; Milisauskas, Sarunas (Polska Akademia Nauk. Instytut Historii Kultury Materialnej, 1990)
Bronocice is a large Neolithic site located at the eastern edge of the Miechów Upland region in southeastern Poland. The objectives of the Bronocice excavations were twofold: 1) to investigate the prehistoric environment, chronology, economy, settlement system, and social organization of Neolithic cultures, and 2) to demonstrate the origin of complex societies in the region. Radiocarbon datingprovides information on the duration and sequence of each occupational phase at Bronocice and therefore is essential to understanding Neolithic chronology and achieving the above-stated objectives. For our study, 27 wood charcoal samples were dated at the Dicarb Laboratory in the United States. Since the samples were selected from the pits containing ceramics, the radiocarbon dates can becompared with the relative chronology of the ceramics. This procedure provided a general, yet a fairly accurate evaluation of the data. The primary results from the radiocarbon dating are as follows: 1) the Bronocice settlement was occupied between 3110±110 be and 2130 ±65 be, and 2) the Bronocice settlement spanned six occupational phases: Lublin-Volynian culture (Lengyel-Polgar cycle in southeastern Poland), Funnel Beaker culture (BR I - I I I phases), and the Baden cycle (BR IV-V).
ill. ; 29 cm
Appendix: Calibration of 14C dates from the Bronocice site
Keywords: Neolithic -- Poland; radiocarbon dating; Bronocice, Działoszyce commune (Poland)

Radiocarbon chronology of the site Dąbki - Pazdur, Mieczysław R. (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 1991)
Radiocarbon chronology of the site Dąbki is based on a set of the dates of charcoal, wood and gyttja. The samples of gyttja were taken from continuous palynological profiles. Obtained radiocarbon dates concentrate in three distinct groups and lead to distinguishing three phases of habitation. Phase I, represented by 3 dates, is dated to 6250 -6150 BP; phase II is represented by 4 dates and its duration may be estimated to 5700 -5600 BP. Available dates are too scarce for estimation of duration of the youngest phase of habitation
ill. ; 29 cm
Keywords: radiocarbon datings; palinology; Dąbki, Darłowo commune (Poland)

The absolute chronology of Late Tripolye sites: a regional approach - Diachenko, Aleksandr; Harper, Thomas K. (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2016)
While numerous studies have attempted to reconcile the relative sequence of Late Tripolye sites with 14C data, results have generally conformed to the general, monolithic periodization of the Cucuteni-Tripolye cultural complex. When viewed as a multi-linear process occurring on the level of numerous interrelated regions, the development of local groups assigned to the periods CI, CI-II and CII can be shown to have a high degree of spatiotemporal variability and overlap. In this article we explore the synchronicity of interactions between groups assigned to different typo-chronological periods and propose a revised hybrid chronology for Late Tripolye development that considers both relative and absolute chronological indicators
ill. ; 25 cm
Keywords: chronology; cultural synchronisms; radiocarbon; Late Tripolye

Dwa grodziska wczesnośredniowieczne w Zawadzie Lanckorońskiej i Naszacowicach - datowanie metodą archeologiczną i dendrochronologiczną - Krąpiec, Marek; Poleski, Jacek (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1996)
The authors present possibilities and limitations in dating the multi-layer and multi-stage sites with help of the archaeological and dendrochronological methods. As the examples they show two fortified settlements from Małopolska region (Naszacowice and Zawada Lanckorońska)
ill. ; 29 cm
Keywords: early Middle Ages; stratigraphy; dating; dendrochronology; independent determinants of chronology

Podstawy dendrochronologii w zastosowaniu do potrzeb archeologii - Gorczyński, Tadeusz (1905–1982) (Zakład Narodowy im. Ossolińskich, 1965)
P. 75-114, [3] leaves of plates : ill. ; 25 cm
Bibliographical footnotes
English summary
Keywords: archaeological research methods; dendrochronology; archaeological wood; dating of wooden monuments

Archeologia Polski. Vol. 15 (1970) No 1, Reviews and discussions - Kopacz, Jerzy. Reviewer (Zakład Narodowy im. Ossolińskich, 1970)
Hans Quitta, Radiocarbondaten und die Chronologie des mittel- und südosteuropäischen Neolithikums, "Ausgrabungen und Funde", t. 12, 1967, No 3, p. 115-125
P. 268-271 ; 25 cm
Bibliographical footnotes
Keywords: Neolithic -- central and southern Europe; chronology of Neolithic; radiocarbon dating

Datowanie radiowęglowe wysokiej precyzji i probabilistyczna kalibracja dat radiowęglowych - Goslar, Tomasz (Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1990)
P. 191-214 : ill., table ; 25 cm
Bibliography p. 210-213
English summary
Keywords: radiocarbon dating; calibration; computer methods in archaeology

Sekwencje stratygraficzne i problemy datowania stanowisk wielowarstwowych - Maetzke, Gabriella (1946–2003) (Zakład Narodowy im. Ossolińskich, 1982)
P. 27-56 : ill. ; 25 cm
Bibliography p. 52-54
French summary
Keywords: stratigraphy; stratigraphic units; multilayered archaeological sities; dating methods

Próba datowania ceramiki wczesnośredniowiecznej metodą termoluminescencji: przykład badań zespołu grodowego w Busównie - Buko, Andrzej (1947– ) (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2008)
P. 25-49 : ill. ; 25 cm
English summary
Bibliography p. 43-47
Keywords: Middle Ages; chronology; strongholds; Polish-Rus frontier; ceramics; thermoluminescence dating method

Holocene climate and human history in the light of radiocarbon dates - Pazdur, Anna (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2013)
The correlation between the chronologies for archaeological settlement and climate conditions is discussed. This relationship is illustrated using an absolute chronology based on 14C dating and the traditional Mesolithic and Neolithic cultural chronology in Central Europe (Poland), set against the background of Late Glacial and Holocene climate change. The fundamental basis for this analysis is the statistical interpretation of dating results, i.e. the method of composite probability density distribution function applied to the series of calibrated radiocarbon dates
ill. ; 24 cm
Keywords: radiocarbon dating; chronology of archaeological culture; climate

Zespoły ceramiczne ze starszych faz wczesnego średniowiecza na wybranych stanowiskach Środkowego Nadodrza w świetle najnowszych wyników datowań przyrodniczych - Gruszka, Bartłomiej; Pawlak, Ewa; Pawlak, Paweł (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2013)
Recent investigations in the middle Oder region have uncovered numerous assemblages of vessels from the older phases of the Early Medieval period. This pottery is characterized by a specific set of formal, stylistic and technological traits. Finds were dated by the thermoluminescence and radiocarbon dating methods and by the dendrochronological method in singular cases. The oldest pottery assemblages were dated to the 6th c. Numerous petrographic analyses helpedto determine the technology used to produce the vessels
ill. ; 25 cm
Keywords: Early Middle Ages; pottery dating; petrographic analyses; thermoluminescence analyses

Corded ware, Fatyanovo and Abashevo culture sites on the flood-plain of the Moskva River - Krenke, Nikolay; Erschov, Ivan; Erschova, Ekaterine; Lazukin, Alexander (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2013)
This article presents new evidence from excavations in the Moskva river valley, where Early Bronze Age sites have been found under alluvial sediments on the flood plain. The finds were identified to the Corded Ware, Fatyanovo and Abashevo cultures. Radiocarbon dates and stratigraphy demonstrate that these sites developed from the middle to the end of the 3rd millennium BC. Analysis of pollen identified ancient fields and provided a general picture of the proportion of wild and culture landscapes
ill. ; 25 cm
Keywords: Corded Ware culture; Fatyanovo; Abashevo; pollen studies; radiocarbon dating

New perspectives of dating prehistoric soil erosion in loess areas = Nowe perspektywy datowania pradziejowej erozji gleb w obszarach lessowych - Poręba, Grzegorz J.; Śnieszko, Zbigniew; Moska, Piotr (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2012)
This study presents the results of Optically Stimulated Luminescence (OSL) dating of colluvial sedimentprofiles from Biedrzykowice and Świerklany in the archaeologically well documented loess area of southernPoland, The method, the criteria for site selection and the limitations of the interpretation of the dates obtainedare discussed. It is shown that Holocene colluvial sediments containing grains of quartz can be approximatelydated using OSL. Despite its many limitations, it remains the only method suitable for direct dating of colluvialsediments. The obtained OSL dates are consistent with the archaeological evidence. The Biedrzykowice profile,located 6 km from the Neolithic settlement at Bronocice, contains two layers of Holocene colluvial sediments.The older layer, OSL dated to 6–5 ka BP, is separated from the younger, medieval layer dated to 1,0–0,5 ka BPby a fossil soil. In Świerklany, where there are no known prehistoric settlements, the accumulation of colluvialsediments only started in the medieval period. The OSL dating confirms earlier assumptions that in naturalHolocene ecosystems in loess areas of the moderate climate forest zones, mineral material was not transportedby slope wash, or only to a minimal extent. This work is the first direct isotopic dating of colluvial sediments inPoland
ill. ; 25 cm
Keywords: luminescence dating; colluvial sediments; Holocene; soil erosion; Neolithic